2013
DOI: 10.1902/jop.2012.120090
|View full text |Cite
|
Sign up to set email alerts
|

Severe Loss of Clinical Attachment Level: An Independent Association With Low Hip Bone Mineral Density in Postmenopausal Females

Abstract: Our study demonstrated that severe CAL was associated with low BMD of the femoral neck and deleterious clinical dental parameters and smoking. Our findings suggest that, in addition to appropriate oral care, individuals with severe CAL may also require additional attention to their systemic bone health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
(97 reference statements)
1
16
0
1
Order By: Relevance
“…Ronderos et al (2000) and Tezal et al (2000) showed significant association between CAL and femoral neck BMD. And, recently, a study has reported that severe CAL was associated with low femoral neck BMD in Brazilian post-menopausal females (Gondim et al 2012). On the other hand, Taguchi et al (2005) reported that self-reported periodontal status was related to lumbar spine BMD, but was not significantly associated with femoral neck BMD in post-menopausal women, and this result is in agreement with this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ronderos et al (2000) and Tezal et al (2000) showed significant association between CAL and femoral neck BMD. And, recently, a study has reported that severe CAL was associated with low femoral neck BMD in Brazilian post-menopausal females (Gondim et al 2012). On the other hand, Taguchi et al (2005) reported that self-reported periodontal status was related to lumbar spine BMD, but was not significantly associated with femoral neck BMD in post-menopausal women, and this result is in agreement with this study.…”
Section: Discussionmentioning
confidence: 98%
“…And, recently, a study has reported that severe CAL was associated with low femoral neck BMD in Brazilian post‐menopausal females (Gondim et al. ). On the other hand, Taguchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus today, several clinical studies suggest an association between osteoporosis and oral bone loss . Recent studies reported in women an association between osteoporosis and tooth loss, indicating that low femoral BMD and T ‐score were associated with fewer remaining teeth . In addition, low BMD and bone stiffness were associated with low number of teeth in women but not in men .…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11][12][13] However, due to the limited availability and cost implications of DXA devices in some regions, the diagnosis of bone disorders may be delayed until the clinical symptoms appear.…”
Section: Introductionmentioning
confidence: 99%